Another step toward DNA selective targeting: NiII and CuII complexes of a Schiff base ligand able to bind gene promoter G-quadruplexes. Issue 18 (7th April 2016) - Terenzi, Alessio; Lötsch, Daniela; van Schoonhoven, Sushilla; Roller, Alexander; Kowol, Christian R.; Berger, Walter; Keppler, Bernhard K.; Barone, Giampaolo
Abstract : Water-soluble Schiff base Ni II complex in the binding pocket of the oncogene G-quadruplex c-Kit1 . Abstract : DNA G-rich sequences are able to form four-stranded structures organized in stacked guanine tetrads. These structures, called G-quadruplexes, were found to have an important role in the regulation of oncogenes expression and became, for such a reason, appealing targets for anticancer drugs. Aiming at finding selective G-quadruplex binders, we have designed, synthesized and characterized a new water soluble Salen-like Schiff base ligand and its Ni II and Cu II metal complexes. UV-Vis, circular dichroism and FRET measurements indicated that the nickel complex can stabilize oncogene promoter G-quadruplexes with high selectivity, presenting no interactions with duplex DNA at all. The same compound exhibited dose-dependent cytotoxic activity in MCF-7 breast cancer cells when combined with lipofectamine as lipophilic carrier.